1971
DOI: 10.1113/jphysiol.1971.sp009416
|View full text |Cite
|
Sign up to set email alerts
|

The inotropic and chronotropic effects of catecholamines on the dog heart

Abstract: SUMMARY1. The chronotropic and inotropic responses of the denervated dog heart to intravenous infusions of noradrenaline, adrenaline and isoprenaline were studied.2. The maximum rate of rise of pressure in the left ventricle of the heart, (dP/dt max) measured at a constant heart rate and mean systemic arterial pressure during each series of infusions, was used as an index of inotropic changes (Furnival, Linden & Snow, 1970).3. The order of potency of the catecholamines in producing both chronotropic and inotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…Firstly, quantitative measurements of the inotropic effects of compounds on the heart are technically difficult and of doubtful reliability when obtained in the presence of the large changes in heart rate and blood pressure which may be caused by doses of isoprenaline and noradrenaline (Furnival et al, 1970;Mason, Braunwald, Covell, Sonnenblick & Ross, 1971). However, previous experiments in carefully controlled preparations have shown that the same relative changes in force and rate are brought about by many compounds which act on the heart through the P-adrenoceptor (Furnival, Linden & Snow, 1971: Harry, Kappagoda, Linden & Snow, 1973Robie, Nutter, Moody& McNay, 1974;Bolter & Ledsome, 1976). In the present series of experiments it was shown that ICI 118,587 produced the same relative changes in the force of contraction for a given change in heart rate as did isoprenaline (Figure, 3).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, quantitative measurements of the inotropic effects of compounds on the heart are technically difficult and of doubtful reliability when obtained in the presence of the large changes in heart rate and blood pressure which may be caused by doses of isoprenaline and noradrenaline (Furnival et al, 1970;Mason, Braunwald, Covell, Sonnenblick & Ross, 1971). However, previous experiments in carefully controlled preparations have shown that the same relative changes in force and rate are brought about by many compounds which act on the heart through the P-adrenoceptor (Furnival, Linden & Snow, 1971: Harry, Kappagoda, Linden & Snow, 1973Robie, Nutter, Moody& McNay, 1974;Bolter & Ledsome, 1976). In the present series of experiments it was shown that ICI 118,587 produced the same relative changes in the force of contraction for a given change in heart rate as did isoprenaline (Figure, 3).…”
Section: Discussionmentioning
confidence: 99%
“…It has already been shown that the endogenous sympathomimetic amines in the blood stream in this dog preparation affect the myocardium (dP/dt max) but do not affect the sino-atrial node and this difference results from the greater uptake of catecholamines by the sympathetic nerves in the sino-atrial node than by those in the muscle (Furnival, Linden & Snow, 1971). Consequently, blockade of,-adrenoceptors in the heart in this preparation produces a reduction in dP/dt max but no change in heart rate (Harry et al, 1973).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Carlsson et al (32) observed in a reserpinized anesthetized cat model that the ratio ofthe drug dose required to produce a 50% maximal chronotropic response to the dose required to produce a 50% maximal inotropic response was 0.93 for the 8,-selective agonist (-) H80/60, 0.5 for the non-subtype selective agonist (-) isoproterenol, and 0.16 for the p32-selective agonist terbutaline. Other authors have reported proportionately greater effects upon heart rate than upon contractility from 82-selective, as opposed to non-subtype selective or /31-selective agents in other experimental preparations (33)(34)(35)(36)(37). induced by PGE1, which we observed in the presence of dobutamine, may reflect beta adrenergic agonist effects of dobutamine that are unopposed by a2-agonist effects.…”
Section: Resultsmentioning
confidence: 30%